An introduction to Scientology - Hubbard, L. Ron (La Fayette Ron), 1911-1986.; Hitchman, Tony.; Golden Era Productions; Scientology Video ([United States] : Scientology Video, 2006)
An interview with L. Ron Hubbard, in which he discusses the origins and practice of Scientology and Dianetics..
DVD release of the 1966 film.
Narrator and interviewer, Tony Hitchman.
DVD.
Keywords: Hubbard, L. Ron -- 1911-1986.; Hubbard, L. Ron -- 1911-1986 -- Interviews; Scientology; Dianetics